Analysis of Financial Recording Accounting and Calculation of Cost Production in The Home Industry to Improve The Economy - Ramadhan (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This study investigates the significance of financial recording accounting and cost production calculation within home industries as a means to enhance local economies. In rural settings like Kelambir Lima Village, where home-based enterprises play a pivotal role in sustaining livelihoods, understanding the efficacy of financial management practices becomes imperative. Through a comprehensive analysis of existing literature and empirical data collected from home industries in Kelambir Lima, this research assesses the current state of financial recording practices and cost production calculation methodologies. Additionally, it examines the impact of these practices on the overall economic well-being of the community. The findings underscore the importance of implementing robust financial recording systems and accurate cost production calculations to streamline operations, improve decision-making processes, and stimulate economic growth at the grassroots level. Furthermore, the study proposes actionable recommendations and strategies to optimize financial management practices within home industries, thereby fostering sustainable development and prosperity in rural communities